2022
DOI: 10.3390/genes13111980
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Nuclear DNA Content in Some Aegilops Species: Best Analyzed Using Flow Cytometry

Abstract: The genera Triticum and Aegilops have been considered as the main gene pool of wheat due to their features, such as tolerance of all types of abiotic and biotic stresses. This study was conducted to evaluate the cytogenetic analyses in 115 native and wild populations from eleven Aegilops species using their nuclear DNA quantification. Mean 2C nuclear DNA contents of different ploidy levels in the wild wheat of Turkey and Iran were measured using the flow cytometry technique. The obtained results showed that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…It is typically measured in picograms (pg) for mass or as the total number of nucleotides in megabase pairs (Mbp), where 1 pg is equal to 978 Mbp of DNA [42]. The genome size is mainly estimated using two cytogenetic methods: flow cytometry and Feulgen micro-densitometry [49][50][51][52]. Previous studies have shown that the high probability of genetic variation among species occurs due to intra-species changes in the nuclear DNA amount [45].…”
Section: Discussionmentioning
confidence: 99%
“…It is typically measured in picograms (pg) for mass or as the total number of nucleotides in megabase pairs (Mbp), where 1 pg is equal to 978 Mbp of DNA [42]. The genome size is mainly estimated using two cytogenetic methods: flow cytometry and Feulgen micro-densitometry [49][50][51][52]. Previous studies have shown that the high probability of genetic variation among species occurs due to intra-species changes in the nuclear DNA amount [45].…”
Section: Discussionmentioning
confidence: 99%